Inhibition of tumor growth and metastasis in pancreatic cancer models by interference with CD44v6 signaling - Matzke-Ogi, Alexandra; Jannasch, Katharina; Shatirishvili, Marine; Fuchs, Beatrix; Chiblak, Sara; Morton, Jennifer; Tawk, Bouchra; Lindner, Thomas; Sansom, Owen; Alves, Frauke; Warth, Arne; Schwager, Christian; et al. (Gastroenterology, 2016)
Background & Aims - Cancer cells with high metastatic potential and stem cell-like characteristics express the cell surface marker CD44. CD44 isoforms that include the v6 exon are co-receptors for the receptor tyrosine kinases MET and Vascular Endothelial Growth factor Receptor-2 (VEGFR-2). We studied CD44v6 signaling in several pancreatic cancer cell lines, and its role in tumor growth and metastasis in several models of pancreatic cancer. - Methods - We analyzed the effects of v6 peptides that interfere with the co-receptor functions of CD44v6 for MET and VEGFR-2 in tumors and metastases grown from cells that express different CD44 isoforms, including CD44v6. The peptides were injected into rats with syngeneic tumors and mice with orthotopic or xenograft tumors. We also tested the effects of the peptides in mice with xenograft tumors grown from patient tumor samples and mice that express an oncogenic form of RAS and develop spontaneous pancreatic cancer (KPC mice). We measured levels of CD44v6 messenger RNA (mRNA) in pancreatic cancer tissues from 136 patients. - Results - Xenograft tumors grown from human cancer cells injected with v6 peptides were smaller and formed fewer metastases in mice. The v6 peptide was more efficient than the MET inhibitor crizotinib and/or the VEGFR-2 inhibitor pazopanib in reducing xenograft tumor growth and metastasis. Injection of KPC mice with the v6 peptide increased their survival time. Injection of mice and rats bearing metastases with the v6 peptide induced regression of metastases. Higher levels of CD44v6 mRNA in human pancreatic tumor tissues were associated with increased expression of MET, tumor metastasis, and shorter patient survival times. - Conclusions - Peptide inhibitors of CD44v6 isoforms block tumor growth and metastasis in several independent models of pancreatic cancer. The v6 peptides induced regression of metastases. Levels of CD44v6 mRNA are increased, along with those of MET mRNA, in patients with metastatic pancreatic tumors, compared with nonmetastatic tumors; the increased levels correlated with shorter patient survival time.
Available online 24 October 2015
Gesehen am 09.06.2020